(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Amphibians are experiencing rapid population declines worldwide due to habitat fragmentation, climate change, pollution, and emerging diseases. As key bioindicators, they play a crucial role in maintaining ecosystem stability. However, habitat fragmentation caused by deforestation, urban expansion, and agricultural activities disrupts their life cycles, isolates populations, and reduces genetic diversity. This study investigates the impact of habitat fragmentation on amphibian biodiversity using ecological and genetic metrics, comparing fragmented and non-fragmented habitats. Key findings indicate a 52% decline in species richness, a 60% reduction in population size, and a 40% decrease in genetic diversity in fragmented habitats. Furthermore, reproductive success drops by 57%, while disease prevalence increases fourfold due to increased environmental stressors and weakened immune responses. Conservation approaches such as habitat restoration, ecological corridors, and protected areas are essential for mitigating these effects. Strategies like wetland conservation, captive breeding, and genetic monitoring can help sustain amphibian populations. Urgent action is required to address habitat fragmentation through policy-driven conservation initiatives and community-based efforts. By implementing targeted restoration strategies and sustainable land-use practices, we can preserve amphibian biodiversity and ensure long-term ecosystem health, preventing further species declines.